2010
DOI: 10.2337/dc10-1135
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Neuropathic Pain in Type 2 Diabetes

Abstract: OBJECTIVENeuropathic pain due to small-fiber sensory neuropathy in type 2 diabetes can be diagnosed by skin biopsy with quantification of intra-epidermal nerve fiber (IENF) density. There is, however, a lack of noninvasive physiological assessment. Contact heat–evoked potential (CHEP) is a newly developed approach to record cerebral responses of Aδ fiber–mediated thermonociceptive stimuli. We investigated the diagnostic role of CHEP.RESEARCH DESIGN AND METHODSFrom 2006 to 2009, there were 32 type 2 diabetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 25 publications
5
35
1
Order By: Relevance
“…Several studies have shown reduced CHEPS amplitudes and prolonged latencies in patients with skin denervation and sensory neuropathy of different causes. [23][24][25][26] Here, we further confirm these findings, suggesting that CHEPS can be used as a reliable, sensitive, and noninvasive measure for Ad thermonociceptive fibers in people with diabetic neuropathy. Our ROC analysis shows the efficacy of CHEPS in detecting nerve fiber abnormalities, comparable to other measures of small and large fiber dysfunction.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have shown reduced CHEPS amplitudes and prolonged latencies in patients with skin denervation and sensory neuropathy of different causes. [23][24][25][26] Here, we further confirm these findings, suggesting that CHEPS can be used as a reliable, sensitive, and noninvasive measure for Ad thermonociceptive fibers in people with diabetic neuropathy. Our ROC analysis shows the efficacy of CHEPS in detecting nerve fiber abnormalities, comparable to other measures of small and large fiber dysfunction.…”
supporting
confidence: 89%
“…[22][23][24] To the best of our knowledge, there have been only two studies specifically investigating the utility of CHEPS in the evaluation of DPN with satisfactory results. 25,26 Both concluded that CHEPS provides a noninvasive and sensitive approach to assess the involvement of small, thermonociceptive nerve fibers in patients with diabetes and that it has great potential for application to interventional studies.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent comparative trial,only two side effects differentiated gabapentin andnortriptyline: dry mouth (more frequent with nortriptyline)and concentration disorders (more frequent with gabapentin). [4] Opioids agonist Oxycodone, tramadol and tramadol/ acetaminophencombination reduce pain in diabetic PPN.Side effects include mainly nausea and constipation,but long-term use of opioids may be associated withmisuse (2.6% in a recent 3-year registry study ofoxycodone in mainly diabetic NP, although higherrates were also reported). [4,34] Tramadol should beused with caution in elderly patients because of risk ofconfusion and is not recommended with drugs actingon serotonin reuptake such as SSRIs.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…The tramadol/acetaminophen combination appears better tolerated. [4] Opioids The Opioids analgesics have unequivocally shown effectiveness in the treatment of PDPN. Whilethese agents, specifically tramadol, oxycodone, and morphine,are recommended as second-line therapy inrecent practice guidelines, their long-term utility has yet to be elucidated.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation